The Charisma Leadership Style of Kyai Haji Arwani Amin The founder of Y anbuul Quran Pesantren, Kudus - Siti Muflichah (Universitas Islam Negeri Alauddin Makassar, 2014)
This paper argues the charisma of a religious leader from Kudus, Central Java Indonesia. As a kyai, he did not only inspire his followers, but also influence them. He was Kyai Haji Arwani Amin, the founder of Yanbu’ul Quran, the biggest pesantren for quranic memorisation in Kudus, and the founder and a mursyid of Tarikat Naqsyabandiah Khalidiah as well. It covers his biography, work and teaching. The perspective of leadership theory is included. Leadership at boarding school is strongly influenced by the type of charismatic leadership. A boarding school kyai as a leader is always synonymous with the type of charismatic leadership. People of the institution also have a very high loyalty to leader. With this type of leadership, boarding school was never abandoned by the people. It has been rarely found that the Islamic boarding school closed down due to lack of its students.